2010
DOI: 10.1007/s00417-010-1369-y
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness, lamina cribrosa and peripapillary scleral histomorphometry in non-glaucomatous chinese eyes

Abstract: In Chinese, central corneal thickness is not significantly correlated with the thickness of the central and peripheral lamina cribrosa and the thickness of the peripapillary sclera nor with the shortest distance between the intraocular space and the cerebrospinal fluid space. These histomorphometric data do not support a relationship between central corneal thickness and thickness of structures of the optic nerve head, and thus do not support an association between a thin cornea and increased structural glauco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 28 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…The fact that we have patients with moderate to advanced disease stage on average in our study possibly explains the CCT difference between groups. It is important to emphasize that this fact probably did not influence our results, as previous studies have not found any relationship between CCT and LC parameters [29,30]. Second, our results apply solely to this specific study population, and should not be extrapolated to glaucomatous patients with different characteristics.…”
Section: Discussionmentioning
confidence: 70%
“…The fact that we have patients with moderate to advanced disease stage on average in our study possibly explains the CCT difference between groups. It is important to emphasize that this fact probably did not influence our results, as previous studies have not found any relationship between CCT and LC parameters [29,30]. Second, our results apply solely to this specific study population, and should not be extrapolated to glaucomatous patients with different characteristics.…”
Section: Discussionmentioning
confidence: 70%
“…11,22,23 For this reason, this device has been used in the current series for evaluating and comparing the anterior and posterior corneal elevation data in eyes with POAG and healthy control subjects. 27,28 Another explanation for our findings could be that the elevation topography and the corneal thickness, in previously normal corneas, do change during the course of the glaucomatous disease, and that this change could be caused by the effect of elevated IOP on the cornea, which may cause mechanical distortion 12 similarly to the IOP-induced mechanical stress observed at the level of the lamina cribrosa. In addition, there were also significant differences, although minimal in magnitude, between glaucomatous and healthy corneas regarding anterior surface elevation.…”
Section: Discussionmentioning
confidence: 79%
“…The disparity may be explained by the duration and severity of glaucoma, which could influence the compliance of the lamina in response to IOP changes [54]. Other studies have found no relationship between CCT and the LC [55,56].…”
Section: Biological Factorsmentioning
confidence: 96%